1988
DOI: 10.1073/pnas.85.21.8227
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thrombin generation and platelet binding on herpes simplex virus-infected endothelium.

Abstract: Atherosclerotic lesions have been reported to contain herpes simplex virus 1 (HSV-1) genomic material. This, and other previous evidence, suggests that latent viral infection may be an atherogenic trigger. Moreover, active HSV-1 lesions manifest marked fibrin deposition in microvessels. In this report we show that very early infection of human endothelial cells with HSV-1 appears to alter surface conformation as detected by merocyanine 540 staining. Concomitantly, the efficiency of prothrombinase complex assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 18 publications
3
53
0
3
Order By: Relevance
“…Studies have demonstrated that infected endothelial cells have increased synthesis of tissue factor, cell surface thrombin expression, platelet adherence, and expression of adhesion molecules, cytokines and growth factors and decrease prostacyclin release (36)(37)(38)(39). Studies have reported that patients with multiple past infections (high pathogen burden) demonstrate endothelial dysfunction, and that the 'pathogen burden' is an independent predictor of endothelial dysfunction (40).…”
Section: Infection and Endothelial Dysfunctionmentioning
confidence: 99%
“…Studies have demonstrated that infected endothelial cells have increased synthesis of tissue factor, cell surface thrombin expression, platelet adherence, and expression of adhesion molecules, cytokines and growth factors and decrease prostacyclin release (36)(37)(38)(39). Studies have reported that patients with multiple past infections (high pathogen burden) demonstrate endothelial dysfunction, and that the 'pathogen burden' is an independent predictor of endothelial dysfunction (40).…”
Section: Infection and Endothelial Dysfunctionmentioning
confidence: 99%
“…Both HCMV and HSV can infect ECs, initiating cellular responses similar to those in atherogenesis. 37,38 Furthermore, HCMV behaves differently in aortic ECs (a vessel susceptible to atheroma) than in brain microvascular ECs (in which atheroma is not found). 39 In aortic ECs, HCMV is nonlytic and is released persistently, whereas in small vessel ECs, it causes rapid lysis.…”
Section: Possible Mechanisms For Virus-induced Accelerated Atherogenesismentioning
confidence: 99%
“…Changes in EC membrane phospholipid topography after herpesviral infection alter the efficiency of assembly of the prothrombinase complex and lead to enhanced thrombin generation. 96 HSV-infected ECs, in the presence of purified prothrombin, factor Va, and factor Xa, generated twofold to threefold more thrombin relative to uninfected ECs. 96 Furthermore, enhanced thrombin production resulted in increased platelet binding to the HSV-infected endothelium.…”
Section: Prothrombotic Effects Of Herpesviral Infection On the Vasculmentioning
confidence: 99%
“…96 HSV-infected ECs, in the presence of purified prothrombin, factor Va, and factor Xa, generated twofold to threefold more thrombin relative to uninfected ECs. 96 Furthermore, enhanced thrombin production resulted in increased platelet binding to the HSV-infected endothelium. Thrombin-induced PGI 2 production by the infected endothelium was substantially reduced.…”
Section: Prothrombotic Effects Of Herpesviral Infection On the Vasculmentioning
confidence: 99%